Hadis di Panggung Dangdut: Takhrīj dan Pembacaan Gadamerian atas Hadis dalam Lirik Lagu Rhoma Irama - Rif'an Akbar; Hilmy Firdausy; Syarifah Rusydah; Hasanuddin Sinaga (Departement of Hadith Sciences, Faculty of Ushuluddin, UIN Syarif Hidayatullah, Jakarta, 2026)
Music occupies an equally important position in the growth and development of Indonesian society in particular. Sometimes music is created in response to social, cultural, or even religious phenomena. Music can also affect the lifestyle, style, and personality of each connoisseur. Dangdut music once occupied the first position in the Skala Survei Indonesia data analysis survey of March 2023 which stated that dangdut was nominated for the most connoisseurs in Indonesia with a percentage of 58.1%, followed by other music genres. Analysis of the content of the Hadith and the validity test of the Hadith in the lyrics of the song is important to ensure the accuracy and authenticity of the religious references conveyed through the song lyrics. Given that music has a strong appeal and memory, the messages conveyed through song lyrics have the potential to influence people's religious understanding and practices. This research uses a qualitative approach with the type of library research. By using two data sources, namely primary and secondary data. Primary data from Hadith books such as al-Kutub al-Tis'ah, al-Mu'jam al-Mufahras li Alfāẓ al-Ḥadīṡ al-Nabawī, and the syarah (commentary) works as an explanation of the meaning. Secondary data uses books, scientific articles, journals, and other literature that are in accordance with the research that the researcher discusses. This research concludes that Hadith can also be conveyed through the medium of music. It is not always the delivery of Hadith that is spoken in discussion forums or lectures, in fact, Rhoma Irama is able to embed religious values in his Dangdut songs. Through the 10 songs taken, all of them have compatibility with the Hadith of the Prophet SAW and of the 10 songs 8 Hadith of Ṣaḥīḥ quality and 2 Hadith of Ḥasan quality with sanad that is Gharīb.